25-{x+[x+(-8)]}=0
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(7x\left(x+1\right)-3\left(x+1\right)=0\Rightarrow\left(x+1\right)\left(7x-3\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}x+1=0\\7x+3=0\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=-1\\x=-\dfrac{3}{7}\end{matrix}\right.\)
b) 3(x + 8) - x2 - 8x = 0
=> 3(x + 8) - (x2 + 8x) = 0
=> 3(x + 8) - x(x + 8) = 0
=> (x + 8)(3 - x) = 0 => \(\left[{}\begin{matrix}x+8=0\\3-x=0\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=-8\\x=3\end{matrix}\right.\)
c) \(x^2-10x=-25\Rightarrow x^2-10x+25=0\Rightarrow\left(x-5\right)^2=0\Rightarrow x=5\)
d) Giống câu c
a) 7x(x+1)−3(x+1)=0⇒(x+1)(7x−3)=07x(x+1)−3(x+1)=0⇒(x+1)(7x−3)=0
⇒[x+1=07x+3=0⇒⎡⎣x=−1x=−37⇒[x+1=07x+3=0⇒[x=−1x=−37
b) 3(x + 8) - x2 - 8x = 0
=> 3(x + 8) - (x2 + 8x) = 0
=> 3(x + 8) - x(x + 8) = 0
=> (x + 8)(3 - x) = 0 => [x+8=03−x=0⇒[x=−8x=3[x+8=03−x=0⇒[x=−8x=3
c) x2−10x=−25⇒x2−10x+
a) \(\left(x-2018\right)\cdot3=0\)
\(\Leftrightarrow x-2018=0\)
\(\Leftrightarrow x=2018\)
b) \(25\left(x-8\right)=0\)
\(\Leftrightarrow x-8=0\)
\(\Leftrightarrow x=8\)
c) \(25+\left(15+x\right)=75\)
\(\Leftrightarrow15+x=50\)
\(\Leftrightarrow x=35\)
b) x(x-4) - 2x+8 = 0
x(x-4) - 2(x-4) = 0
(x-2) (x-4) = 0
TH1: x-2=0 TH2: x-4=0
x=2 x=4
Vậy x\(\in\){2;4}
\(b,\Leftrightarrow\left(x-4\right)\left(x-2\right)=0\Leftrightarrow\left[{}\begin{matrix}x=2\\x=4\end{matrix}\right.\\ c,\Leftrightarrow\left(x-5\right)\left(x+5\right)-\left(x+5\right)=0\\ \Leftrightarrow\left(x+5\right)\left(x-6\right)=0\Leftrightarrow\left[{}\begin{matrix}x=6\\x=-5\end{matrix}\right.\\ d,\Leftrightarrow\left(2x-1\right)^2-\left(2x-1\right)\left(2x+1\right)=0\\ \Leftrightarrow\left(2x-1\right)\left(2x-1-2x-1\right)=0\\ \Leftrightarrow x=\dfrac{1}{2}\\ e,\Leftrightarrow\left(3x-1-x-5\right)\left(3x-1+x+5\right)=0\\ \Leftrightarrow\left(2x-6\right)\left(4x+4\right)=0\\ \Leftrightarrow\left[{}\begin{matrix}x=-1\\x=3\end{matrix}\right.\\ f,\Leftrightarrow\left(x-2\right)\left(x^2+2x+4\right)-\left(x-2\right)\left(x-12\right)=0\\ \Leftrightarrow\left(x-2\right)\left(x^2+x+16\right)=0\\ \Leftrightarrow\left[{}\begin{matrix}x=2\\\left(x+\dfrac{1}{2}\right)^2+\dfrac{63}{4}=0\left(vô.n_0\right)\end{matrix}\right.\\ \Leftrightarrow x=2\)
\(\left(x-2\right)\left(4x-20\right)=0\\ \Rightarrow\left[{}\begin{matrix}x-2=0\\4x-20=0\end{matrix}\right.\\ \Rightarrow\left[{}\begin{matrix}x=2\\4x=20\end{matrix}\right.\\ \Rightarrow\left[{}\begin{matrix}x=2\\x=5\end{matrix}\right.\\ \left(x-5\right)\left(25-5x?\right)=0\\ \Rightarrow\left[{}\begin{matrix}x-5=0\\25-5x=0\end{matrix}\right.\\ \Rightarrow\left[{}\begin{matrix}x=5\\5x=25\end{matrix}\right.\\ \Rightarrow\left[{}\begin{matrix}x=5\\x=5\end{matrix}\right.\\ \left(x-4\right)\left(2x-8\right)\\ \Rightarrow\left[{}\begin{matrix}x-4=0\\2x-8=0\end{matrix}\right.\\ \Rightarrow\left[{}\begin{matrix}x=4\\2x=8\end{matrix}\right.\\ \Rightarrow\left[{}\begin{matrix}x=4\\x=4\end{matrix}\right.\)
a,(x-2)(4x-20)=0
=>x-2=0 hoặc 4x-20=0
=>x=2 hoặc x=5
b,(x-5)(25-5)=0
=>x-5=0 ( vì 25-5 ≠0)
=>x=5
c,(x-4)(2x-8)=0
=>x-4=0 hoặc 2x-8=0
=>x=4
\(a,96-3\left(x+8\right)=42\\ \Rightarrow3\left(x+8\right)=54\\ \Rightarrow x+8=18\\ \Rightarrow x=10.\\ b,15.5\left(x-25\right)-225=0\\ \Rightarrow75\left(x-25\right)-225=0\\ \Rightarrow75\left(x-25\right)=225\\ \Rightarrow x-25=3\\ \Rightarrow x=28.\\ c,250:x+15=25\\ \Rightarrow250:x=10\\ \Rightarrow x=25\\ d,36:\left(x-5\right)=2^2\\ \Rightarrow36:\left(x-5\right)=4\\ \Rightarrow x-5=9\\ \Rightarrow x=14.\\ e,\left[3.\left(70-x\right)+5\right]:2=46\\ \Rightarrow3.\left(70-x\right)+5=92\\ \Rightarrow3\left(70-x\right)=87\\ \Rightarrow70-x=29\\ \Rightarrow x=41.\)
\(a,\left(-31\right).\left(x+7\right)=0\\ \Rightarrow x+7=0\\ \Rightarrow x=-7\\ b,\left(8-x\right).\left(x+13\right)=0\\ \Rightarrow\left[{}\begin{matrix}8-x=0\\x+13=0\end{matrix}\right.\\ \Rightarrow\left[{}\begin{matrix}x=8\\x=-13\end{matrix}\right.\\ c,\left(x^2-25\right)\left(3-x\right)=0\\ \Rightarrow\left(x-5\right)\left(x+5\right)\left(3-x\right)=0\\\Rightarrow \left[{}\begin{matrix}x-5=0\\x+5=0\\3-x=0\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=5\\x=-5\\x=3\end{matrix}\right.\\ d,\left(x-3\right)\left(x^2+4\right)=0\\ \Rightarrow\left[{}\begin{matrix}x-3=0\\x^2+4=0\end{matrix}\right.\\ \Rightarrow\left[{}\begin{matrix}x=3\\x^2=-4\left(loại\right)\end{matrix}\right.\\ \Rightarrow x=3\)
25−(𝑥+[𝑥+(−8)])=0
⇔25−(𝑥+[𝑥−8])=0
⇔25−(𝑥+𝑥−8)=0
⇔25−(2𝑥−8)=0
⇔25−2𝑥+8=0
⇔33−2𝑥=0
⇔−2𝑥+33=0
⇔𝑥=\(\dfrac{33}{2}\)
25−(𝑥+[𝑥+(−8)])=0
⇔25−(𝑥+[𝑥−8])=0
⇔25−(𝑥+𝑥−8)=0
⇔25−(2𝑥−8)=0
⇔25−2𝑥+8=0
⇔33−2𝑥=0
⇔−2𝑥+33=0
⇔𝑥=332